The Promise of Research to Advance Smart Decarceration - Epperson, Matthew W. (Criminal justice and behavior, 2021)
This paper describes the concept of “Smart Decarceration” and introduces the special issue of Criminal Justice and Behavior entitled “Research to Advance Smart Decarceration Policies, Programs, and Interventions.” The concept of Smart Decarceration originated nearly a decade ago as the United States reached a tipping point in mass incarceration, and it focuses on three interrelated outcomes: substantially reducing the use of incarceration and other forms of punishment; reversing racial disparities and other inequities in the criminal justice system; and promoting safety and well-being, particularly for communities that have been most impacted by mass incarceration. Ultimately, Smart Decarceration efforts should prioritize reducing the overall footprint of the criminal justice system, while building capacity outside of the system to support safety, health, and well-being. Research plays a critical role in advancing Smart Decarceration, as new forms of knowledge and evidence must be developed to replace ineffective and unjust policies and practices associated with mass incarceration. The paper discusses approaches to research that move beyond typical criminal justice outcomes and focus on the multifaceted goals of Smart Decarceration. The six articles in this special issue are introduced, highlighting their foci across ecological levels and the breadth of the criminal justice continuum, centering populations most impacted by incarceration, and identifying practice and policy innovations.